Augmented Reality Sebagai Media Edukasi Pengenalan Anggota Keluarga Pada Anak: Studi Kasus Penggunaan Buku Interaktif - Setyo Kurniawati, Lintang; Fitriyah, Nur Qodariyah; Fitriyah, Bait Syaiful Rijal; Fitriyah, Aurelia Agustin; Fitriyah, Cetta Ugama Putra (Jurnal Teknik, 2025)
This study develops an educational media based on Augmented Reality (AR) in the form of an interactive book to introduce family members to early childhood learners. AR technology enables more engaging visual interaction compared to conventional learning methods. The research method used is Research and Development (R&D) with stages including needs analysis, design, development, implementation, and evaluation. The trial results indicate that this media significantly improves children's understanding of family members, with a statistically significant increase in post-test scores compared to pre-test (p < 0.05). Evaluations from teachers and parents also show that this media is effective, engaging, and easy for children to use. Therefore, AR-based interactive books have the potential to be an innovative solution in early childhood education.